IMPLEMENTATION OF DIVERSION TOWARDS CHILDREN WHO COMMIT CRIMINAL ACTS OF ABUSE IN THE JURISDICTION OF PEKANBARU CITY - Jahri, Ilfan Afriandi; Asnawi, Eddy; Pardede, Rudi (EKSEKUSI, 2024)
This research aims to analyze the application of diversion to children who commit criminal acts of abuse in the jurisdiction of Pekanbaru City and analyze the obstacles and efforts to overcome these obstacles. The type of research used is sociological legal research with a legal effectiveness approach. The data source used is primary data which is analyzed qualitatively. The results of the research show that the implementation of diversion against children who have committed criminal acts of abuse in the jurisdiction of Pekanbaru City has not been implemented well in 2021 to 2023, where there is still failure to diversion against children who have committed serious criminal acts of abuse. Some of the obstacles behind this failure include: First, legal factors, namely legal provisions that require an agreement between the perpetrator and the victim for diversion, whereas there is no agreement on compensation. Second, the factor of law enforcement officers, namely: the lack of involvement of the Pekanbaru City Social Service in the diversion process. Third, community factors, namely: The desire of the community that the perpetrator must be punished.Keywords: Diversion, Children, Criminal Abuse